Product Marketing Development Strategies in Sade Tourism Village for Increasing the Number of Tourist Visits - Firman Koma Febdilan; Siti Lathifah (Faculty of Economics and Business, University of Mataram, 2023)
The purpose of this research is to find out how the people of Sade Rembitan Hamlet sell products, positioning, promotion, place, sales process, cooperation system, and tourist response. The method used in this research is a qualitative approach by using a phenomenological design. collecting data using three techniques. such as observation, documentation, and interviews. The results of this study are in marketing their products, the residents of Sade Hamlet have not been able to market their products due to a lack of understanding of foreign languages. so that the impact on product positioning, promotion, and interaction with tourists is hampered. Besides that, the price of the products sold must have a price list so that there is no price competition and does not confuse tourists confused by the different price variations among other sellers. Sade Hamlet tourism products benefit from the customs and traditions that still exist today. Thus, the promotion carried out by the residents of Sade Hamlet is currently still in the category of being promoted by cooperation partners from industry, related governments, HPI associations, and visiting tourists. Thus, the process of interaction, cooperation with local guides and travel agents is very well established. However, it does not rule out the possibility of having to maintain intense communication between them.